Anarchism, utopianism and hospitality: the work of René Schérer. (2nd April 2016) - Morgan, Diane
Abstract: René Schérer (born 1922) is lamentably almost unknown to the Anglo-American world as his work has, as yet, not been translated. He is one of the main specialists of the French 'utopian socialist', Charles Fourier (1772–1837), and a major thinker in his own right. He is the author of more than twenty books and co-editor of the journal Chimères. Colleague and friend at Vincennes University (Paris 8) of Michel Foucault, Gilles Deleuze, Félix Guattari, Jacques Derrida, Jacques Rancière, Jean-François Lyotard, François Châletet, Alain Brossat, Georges Navet, Miguel Abensour, Pierre Macherey..., he continues to host seminars at Paris 8 (now located at Saint-Denis). He is a living testimony to a radical past, and a continuing inspiration to a new generation of young thinkers. This article aims to convey the original specificity of his understanding of anarchism. By so doing, it will stress the importance of his work for any thinking concerned with a politicised resistance to social conformity and the supposed 'state of things' today.